2010
DOI: 10.1371/journal.pone.0013069
|View full text |Cite
|
Sign up to set email alerts
|

Hfq Is a Global Regulator That Controls the Pathogenicity of Staphylococcus aureus

Abstract: The Hfq protein is reported to be an RNA chaperone, which is involved in the stress response and the virulence of several pathogens. In E. coli, Hfq can mediate the interaction between some sRNAs and their target mRNAs. But it is controversial whether Hfq plays an important role in S. aureus. In this study, we found that the deletion of hfq gene in S. aureus 8325-4 can increase the surface carotenoid pigments. The hfq mutant was more resistant to oxidative stress but the pathogenicity of the mutant was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 44 publications
2
79
3
1
Order By: Relevance
“…Hfq is present in most of the staphylococcal genomes, but differentially expressed (Liu et al, 2010). Its role in vivo is still controversial, while an hfq deletion mutant has no significant phenotype (Bohn et al, 2007;Romilly et al, 2012a).…”
Section: Hfq Protein a Mysterious Protein In S Aureusmentioning
confidence: 99%
“…Hfq is present in most of the staphylococcal genomes, but differentially expressed (Liu et al, 2010). Its role in vivo is still controversial, while an hfq deletion mutant has no significant phenotype (Bohn et al, 2007;Romilly et al, 2012a).…”
Section: Hfq Protein a Mysterious Protein In S Aureusmentioning
confidence: 99%
“…11 The reason why Hfq cannot be detected has not been yet investigated although it was suggested that mutations in the promoter region led to a significant decrease of hfq transcription. 11 Interestingly, a recent work 92 showed that Hfq is detected only in several clinical strains and in the 8325-4 strain but not in COL and RN6390, two laboratory-adapted strains. 11,63 In 8325-4, where Hfq is expressed, its deletion decreases pathogenicity in a murine peritonitis infection model.…”
Section: Is There a Specific Machinery Associated With Srna Function?mentioning
confidence: 99%
“…An RNase E-Hfq-sRNA complex is thought to function in translational repression and subsequent mRNA destabilization and degradation (Morita et al, 2005;Morita et al, 2006). Additional functions of Hfq include ATPase activity (Sukhodolets & Garges, 2003), cellular stress response and modulation of virulence in some bacterial strains (Tsui et al, 1994;Fantappie et al, 2009;Liu et al, 2010). Interestingly, the virulence of the multi-drug resistant human pathogen S. aureus was decreased in Hfq-deletion strains.…”
Section: Specific Functions Of Bacterial Hfqmentioning
confidence: 99%
“…Interestingly, the virulence of the multi-drug resistant human pathogen S. aureus was decreased in Hfq-deletion strains. (Liu et al, 2010).…”
Section: Specific Functions Of Bacterial Hfqmentioning
confidence: 99%